WOODEN BRIDGES IN AMAZONIA: RECOMMENDING REGIONAL FOREST SPECIES FOR STRUCTURAL MAINTENANCE - Ibanez Dutra Munhoz; Marcos Cesar de Moraes Pereira; Adriano José Nogueira Lima; Estevão Vicente Cavalcanti Monteiro de Paula (Revista Árvore)
ABSTRACT Wooden bridges are essential structures for communities, especially in the Amazon region, where they have played a crucial role in territorial unification. Most were built without the supervision of specialized technicians. Maintenance of these structures is essential to ensure their durability, given the use of different wood species and the challenges of natural degradation. This study aims to list suitable Amazonian species for each structural element of DNITtype bridges (Brazilian National Department of Transport Infrastructure), taking into account natural durability, mechanical strength and dimensional stability. The justification lies in the need to increase the useful life of these structures, taking into account factors such as environmental degradation and biological attacks. To this end, bibliographic data on the species identified in two bridges on the BR319 was studied, selecting and separating them into groups, for use at points most susceptible to attack and points subject to the weather, which meet the structural calculation, and also have good dimensional stability. The results listed eigth possible forest species for appropriate use in the maintenance of DNITtype Amazonian wooden bridges.